Dynamic analysis of the water, food, and energy nexus in minab county: An integrated approach to sustainable water resource management in hormozgan province - Mahdiye Amani; Maryam Omidi Najafabadi; Seyed Mehdi Mirdamadi; Ali Mohammadi Torkashvand (Results in Engineering, 2025)
This study addresses the water scarcity crisis in Minab County, Hormozgan Province, by assessing the sustainability of water resources using a system dynamics approach. The analysis focuses on measuring both the physical and economical water productivity, as well as energy productivity, for five key agricultural products—wheat, barley, tomato, onion, and watermelon—under climate change conditions. Findings reveal that although watermelon exhibits the highest efficiency in water and energy use, with a physical water productivity of 8.23 kg/m³ and an energy intensity of 88 MJ/ha, it ranks lower in priority based on the composite Food-Water Index (FWI) due to its limited contribution to food security. Conversely, tomatoes demonstrate the highest economic water productivity at 0.0408 USD/m³, reflecting their high market value and economic importance. Scenario analyses predict an 80 % decline in water security and a 32 % increase in energy demand under projected population growth. Expanding the cultivated area by 30 % is estimated to improve food security by 25–30 %, though it necessitates the adoption of smart water management practices. The integration of Water–Energy–Food (WEF) Nexus policies—aimed at reducing water demand by 30 % while increasing food production to 45 million tons by 2050—emerged as the optimal strategy to balance population needs and limitations of the resources. The study underscores the critical need for implementing integrated policies based on sustainability indicators, strategic crop planning, and coordinated resource management to ensure long-term food security and ecological resilience. The analysis identifies wheat and barley as critical stress points due to their low water productivity but high food security reliance, while watermelon presents a paradox of high resource efficiency but minimal strategic value. The study highlights the trade-offs between food security and resource use efficiency at the core of the water–energy–food nexus.